Opportunistic Screening for Raised Blood Sugar and Diagnosing Prediabetes and Diabetes among Patients Coming for Eye, ENT Consultation: A Descriptive Study (MedS Alliance Journal of Medicine and Medical Sciences, 2022)
INTRODUCTION: Diabetes is a pandemic of public health importance, and prediabetes has also emerged as a major public health concern. Unfortunately, one-third of individuals with diabetes are identified only after developing complications, and nearly three-fourths are unaware of their raised blood sugar status. Opportunistic screening at an earlier stage has good prognosis. The study aimed at an opportunistic screening of raised plasma glucose levels of outpatients and diagnosing prediabetes and diabetes among them. MATERIALS AND METHODS: This descriptive cross-sectional study was conducted among patients visiting an Eye ENT hospital in Bhaktapur, Nepal, between January to December 2019. Outpatients aged 40-79 years with unknown history of diabetes were invited for free hyperglycemia screening. Descriptive analysis was computed for patients participating in random plasma glucose (RPG) screening and patients coming for definitive tests for diabetes with elevated RPG levels. RESULTS: Amongst 6,913 outpatients, 14.9% had RPG levels of 140 mg/dL and higher. Among 159 patients with RPG levels 140 mg/dL and higher, 40.9% had prediabetes, and 32.7% had diabetes. CONCLUSIONS: Opportunistic screening in hospital OPD settings is feasible to identify people at risk of hyperglycemia. Timely detection of a silent killer - diabetes and prediabetes can be useful for early intervention and preventing complications.